Pengaruh Penambahan Limbah Sisa Penyaringan Minyak Kelapa Sawit Sebagai Bahan Tambah Terhadap Kuat Tekan Dan Kuat Lentur Beton - Muhammad Gala Garcya; Zulfikar Djauhari; Alex Kurniawandy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The research aims to obtain the characteristic of concrete using Spent Bleaching Earth (SBE) as substitute material on normal concrete. It is focused on compressive strength, setting time, and flexure strength. The percentage of SBE it used are 0%, 2%, and 4% of the cement weight. The result show SBE is not suitable to be a cement replacement because it show the decrease of compressive and flexure strength. But the setting time on SBE is slower than 0% SBE substitution and need more time to harden than normal concrete.Keywords : Spent Bleaching Earth, setting time, compressive strength, flexure strength